Grand multiparity and the possible risk of adverse maternal and neonatal outcomes: a dilemma to be deciphered - Ghadeer K. Al-Shaikh; Gehan H. Ibrahim; Amel A. Fayed; Hazem Al-Mandeel (BMC, 2017)
Abstract Background The relation between grand multiparity (GMP) and the possible adverse pregnancy outcomes is not well identified. GMP (parity ≥5 births) frequently occurs in the Arab nations; therefore, this study aimed to identify the correlation between GMP and the different adverse maternal and neonatal outcomes in the Saudi population. Method This cohort study was conducted on a total of 3327 women from the labour ward in King Khaled University Hospital, Riyadh, Saudi Arabia. Primiparous, multiparous and grand multiparous females were included. Socio-demographic data and pregnancy complications like gestational diabetes or hypertension, preeclampsia and intrauterine growth restriction were retrieved from the participants' files. In addition, the labour ward records were used to extract information about delivery events (e.g. spontaneous preterm delivery, caesarean section [CS]) and neonatal outcomes including anthropometric measurements, APGAR score and neonatal admission to the intensive care. Results Primiparas responses were more frequent in comparison to multiparas and GMP (56.8% and 33%, and 10.2% respectively). In general, history of miscarriage was elevated (27.2%), and was significantly higher in GMP (58.3%, p < 0.01). Caesarean delivery was also elevated (19.5%) and was significantly high in the GMP subgroup (p < 0.01). However, after adjustment for age, GMP were less likely to deliver by CS (odds ratio: 0.6, 95% CI: 0.4-0.8; p < 0.01). The two most frequent pregnancy-associated complications were gestational diabetes and spontaneous preterm delivery (12.6% and 9.1%, respectively). The former was significantly more frequent in the GMP (p < 0.01). The main neonatal complication was low birth weight (10.7%); nevertheless, neonatal admission to ICU was significantly higher in GMP (p = 0.04), and low birth weight was more common in primiparas (p < 0.01). Furthermore, logistic regression analysis revealed an insignificant increase in the maternal or neonatal risks in GMP compared to multiparas after adjustment for age. Conclusion Grand multiparous Saudi females have similar risks of maternal and neonatal complications compared to the other parity groups. Advanced age might play a major role on pregnancy outcomes in GMP. Nevertheless, grand multiparty might not be discouraged as long as women are provided with good perinatal care.